(3GdeQJHg GdQGHYI aj fSH QShd Gddg Udi Gddg Ydjg hSde hSjQg heZGRjg hLed ef GdJGQjNs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s ((3eMeO Hf CMeO Hf CHj HcQ GdMfai s)
(3ChdgG (B:s
(3Chdg HGH fSH QShd Gddg s
(3BNQgG (B:s
(3bO GYGf Gdg JYGdi Ydi GSJjaGA s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B272 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs